Intuitions of justice and the utility of desert - Robinson, Paul H., 1948- (Oxford : Oxford University Press, 2013)
Research suggests that people of all demographics have nuanced and sophisticated notions of justice. Intuitions of Justice and the Utility of Desert sketches the contours of a wide range of lay judgments of justice, touching many if not most of the issues that penal code drafters or policy makers must face.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Criminal justice, Administration of -- Philosophy; Criminal justice, Administration of -- Public opinion; Criminal justice, Administration of -- Moral and ethical aspects; Criminal law -- Philosophy; Criminal law -- Public opinion; Criminal law -- Moral and ethical aspects